Pola Komunikasi Antarbudaya Batak dan Jawa di Yogyakarta - Adi Bagus Nugroho; Puji Lestari; Ida Wiendijarti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2012)
Yogyakarta City is one of the multiethnic cities in Indonesia, the majority of which are migrants who are students studying at UPN